2015
DOI: 10.2807/1560-7917.es2015.20.18.21115
|View full text |Cite
|
Sign up to set email alerts
|

The Italian registry of cystic echinococcosis (RIEC): the first prospective registry with a European future

Abstract: Cystic echinococcosis (CE), a worldwide zoonosis, is highly endemic in southern and eastern Europe. Its actual prevalence is unknown due to the lack of efficient reporting systems designed to take into account the particular features of the disease. Neglect of CE makes diagnosis and clinical management difficult outside referral centres, with inconsistencies in clinical practice and often unnecessary procedures carried out that have associated risks and costs. The Italian registry of CE (RIEC) is a prospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
(24 reference statements)
1
25
0
1
Order By: Relevance
“…A descriptive summary of the available scientific evidence and uncertainties is provided for all TORs. This is based on the systematic literature reviews carried out under the EFSA Grant Project GP/EFSA/AHAW/2012/01 (Echinococcus multilocularis infection in animals; Casulli et al, 2015) and on review of additional scientific papers (mainly published after the systematic review) and the data sources mentioned in section 2.1.…”
Section: Methodologies 22mentioning
confidence: 99%
See 2 more Smart Citations
“…A descriptive summary of the available scientific evidence and uncertainties is provided for all TORs. This is based on the systematic literature reviews carried out under the EFSA Grant Project GP/EFSA/AHAW/2012/01 (Echinococcus multilocularis infection in animals; Casulli et al, 2015) and on review of additional scientific papers (mainly published after the systematic review) and the data sources mentioned in section 2.1.…”
Section: Methodologies 22mentioning
confidence: 99%
“…In a Systematic Review on the risk factors for introduction, transmission and establishment of EM in free areas through movements of domestic and wildlife species involved in the EM lifecycle (Casulli et al, 2015), the only eligible publication of Stieger et al (2002) analysed the high prevalence of EM reported from foxes in the city of Zurich, Switzerland. This work shows that differences in the prevalence, habitats and ecology of definitive and intermediate hosts may influence the risk of transmission and establishment of the parasite in urban and peri-urban areas.…”
Section: Probability Of Transmission and Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…and Italy and the Mediterranean countries are considered endemic . In Italy, the prevalence in 2014, estimated on hospital discharge records, is up to 1.06/100 000 inhabitants/year, but it is expected that these data are underestimated as outpatients or asymptomatic patients are not included in the analysis . CE diagnosis and clinical management are based on ultrasound (US).…”
Section: Introductionmentioning
confidence: 99%
“…), which all contribute to the transmission of E. granulosus leading to a high rate of infection, particularly in small ruminants Varcasia et al, 2011). Several papers have been published on CE in Sardinia, as this island represent a good epidemiological model (Conchedda et al, 2010;Kinkar et al, 2016;Scala et al, 2006;Tamarozzi et al, 2015;Varcasia et al, 2004Varcasia et al, , 2011. However, the role of cattle in the epidemiology and transmission of CE has always been questioned, as these large ruminants are often found be infected with non-host-specific Echinococcus species.…”
Section: Introductionmentioning
confidence: 99%